STRUKTUR MODAL DAN KINERJA PERUSAHAAN DENGAN PERTUMBUHAN PERUSAHAAN SEBAGAI MEDIASI - Sera Veronika; Kadarusman Kadarusman (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2020)
This study aims to analyze the effect of capital structure on firm performance with firm growth as an intervening variable. In this study, the capital structure variable is measured by the DAR and DER indicators. Firm performance variables are measured by ROA and ROE indicators. Firm growth variable is measured by AGR and SGR indicators. The object of research used was a manufacturing industry company in 2018 which was listed on the Indonesia Stock Exchange. This study uses a purposive sampling technique in determining research samples. Obtained 50 companies as research samples in accordance with predetermined sample criteria. Data analysis method in this research is partial least square (PLS) analysis using smartPLS 3.0 application. The results of this study the capital structure has a significant negative effect on firm performance. Capital structure has a significant positive effect on firm growth. Firm growth has a significant positive effect on firm performance. Firm growth becomes a partial mediating variable in the relationship of capital structure to firm performance.